Anxiety Management through an Islamic Spiritual Approach - Mukarrami, Nur Fadhillah; Syahidin, S; Sumarna, Elan (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Anxiety is a condition that is often experienced by everyone. However, if the anxiety felt is excessive, then this is the beginning of the trigger for mental illnesses. The purpose of this study is to find out what anxiety is and how to deal with it spiritually. The research method used in this study is the library research method. The findings of the research are the key to the cure of anxiety, namely as Q.S. Ar-Ra'd/13 verse 28, which explains how to calm the anxious heart by remembering Allah. The meaning of remembering Allah here is not just remembering the name of Allah, but by being 100% sure that Allah is the only helper. Instill in your heart that faith in Allah exists.